Genetic characterization of some wild grape populations (Vitis vinifera subsp. sylvestris) of Zagros mountains (Iran) to indentify a conservation strategy. Issue 1 (24th April 2014) - Doulati-Baneh, Hamed; Mohammadi, Seyed Abolghasem; Labra, Massimo; De Mattia, Fabrizio; Bruni, Ilaria; Mezzasalma, Valerio; Abdollahi, Rahim
Abstract : In this study, the genetic constitution of wild grape populations distributed in the Zagros Mountains in the north-west part of Iran was investigated to assess their risk of extinction and to identify the most suitable conservation strategy. A total of 65 wild grapevine samples from five different populations were analysed using 23 SSR loci. Consistent allelic richness was detected in all the analysed populations (from 4.01 to 5.35). The observed heterozygosity and expected heterozygosity were high with mean values of 0.67 and 0.69, respectively. A modest heterozygosity deficiency was detected only in the Piranshahr and Sardasht-Shalmash populations. The neighbour-joining dendrogram clustered the accessions into three groups corresponding to the geographical distribution of the populations. Molecular data combined with field evaluation revealed that an ex situ conservation approach is the most suitable strategy for preserving the genetic richness of Iranian wild grape populations with consistent rare alleles (about 20%). We propose in situ preservation only in the case of the Sardasht-Ghasmarash population to ensure that evolutionary dynamic forces continue to influence plant adaptation and survival in response to environmental alterations.